Association of chronotype, breakfast habits, and sleep quality with BMI-for-Age in adolescents - Tasya Ardia Selviana; Anik Lestari; Eti Poncorini Pamungkasari (AcTion: Aceh Nutrition Journal, 2025)
Adolescence is prone to nutritional imbalances. Research in SMPN 18 Surakarta showed that 50% of adolescents were thinned, 10% were overweight, and 3,3% were obese. This study aimed to analyze whether chronotype, breakfast habits, and sleep quality contribute to malnutrition among adolescents. This research was conducted in Surakarta City between November 2024-January 2025 and used a cross-sectional as the design with multistage sampling. The Lemeshow Formula showed that the minimum sample size was 106. The instruments used were MEQ, Breakfast Habits, and PSQI questionnaires as well as body weight and height measurements. Kolmogorov-Smirnov test showed that the data is normally distributed. Pearson used as the bivariate test and multiple linear regression as the multivariate test. There was no correlation between chronotype (p = 0,900; r = 0,011), breakfast habits (p = 0,298; r = 0,087), and sleep quality (p = 0,420; r = 0,067) and BMI-for-age. There was no correlation between all independent variables and the dependent variable (F = 0,585). This research concluded that there is no correlation between chronotype, breakfast habits, and sleep quality with BMI-for-age in adolescents. However, further research with more diverse subjects and lifestyle variables is required to confirm these findings.